“Liver–gut” axis: A target of traditional Chinese medicine for the treatment of non-alcoholic fatty liver disease - Guo, Kangxiao; Xu, Sisheng; Zeng, Zhaofeng (Frontiers in Endocrinology, 2022)
Non-alcoholic fatty liver disease (NAFLD) occurs when fat accumulates in the liver even without excessive alcohol intake. Among the current therapeutic approaches for NAFLD, lifestyle modification with dietary changes and regular exercise is the mainstay treatment. With the rise of intestinal microecology, regulation of the “liver–gut” axis can be an effective treatment for NAFLD. This review aimed to assess the modulation of the liver–gut microbiota axis with traditional Chinese medicine (TCM) as a therapeutic approach to NAFLD and further explored its application in the newly discovered therapeutic avenues beyond NAFLD treatment.